Experimental and computational evaluation of illicium verum as a novel eco‐friendly corrosion inhibitor for aluminium. Issue 1 (17th August 2017) - Ladha, D. G.; Shah, N. K.; Ghelichkhah, Z.; Obot, I. B.; Khorrami Dehkharghani, F.; Yao, J.‐Z.; Macdonald, D. D.
Abstract : Illicium verum extract is investigated as a corrosion inhibitor of aluminium in the presence of an acid medium using gravimetric and impedance techniques. The gravimetric results reveal that the adsorption of inhibitor on the metal surface is physisorption. The impedance measurements are used to interpret the electrochemical process occurring at the interface of aluminium and corrosive medium. The surface characteristics of aluminium are evaluated using scanning electron microscopy‐energy dispersive X‐ray spectroscopy. The percentage composition of chemical constituents present in the extract is obtained using gas chromatography‐mass spectrometry and E‐anethole is found to be the main chemical component. The interaction between the chemical constituents or inhibitor molecules and the metal surface are evaluated using Monte Carlo simulation. The determination of electron density on the inhibitor molecules is performed using density functional theory. The results from this respective study demonstrate good inhibitive properties of the illicium verum extract towards the corrosion of aluminium in concentrated hydrochloric acid solution. Abstract : Illicium verum extract (IVE) acts as a good corrosion inhibitor for aluminium in hydrochloric acid. The result is experimentally proved by EIS and gravimetric measurements. SEM images show that IVE reduces the corrosion rate of Al. Monte Carlo simulations are performed to study the interaction between all the major chemical constituents of inhibitor and the metal surface.